2000
DOI: 10.1007/s002689910084
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Gossypibomas: The Need to Count Sponges

Abstract: Intraperitoneal forgotten foreign bodies are prone to create adhesions and to encapsulate, or to provoke an exudative response, with or without accompanying bacterial infection. Often a process of self-extrusion is initiated. This is also true for gossypibomas, retained surgical sponges. Presentation is possible as a pseudotumoral, occlusive, or septic syndrome; several cases, however, have remained asymptomatic for as long as several decades. Ultrasonography and radiology (especially computed tomography) cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
119
0
12

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 59 publications
4
119
0
12
Order By: Relevance
“…Unfortunately, delayed diagnosis is usually associated with high morbidity and mortality. The morbidity and mortality rate was reported at a high rate of 50 and 11-35 %, respectively, which is compatible with our study 50 and 7 % [24]. The most common reason of these high rates is sepsis related to intraabdominal abscess, as in our case.…”
Section: Discussionsupporting
confidence: 79%
“…Unfortunately, delayed diagnosis is usually associated with high morbidity and mortality. The morbidity and mortality rate was reported at a high rate of 50 and 11-35 %, respectively, which is compatible with our study 50 and 7 % [24]. The most common reason of these high rates is sepsis related to intraabdominal abscess, as in our case.…”
Section: Discussionsupporting
confidence: 79%
“…10,11 Gawande et al 12 reported that the incidence of retained textilomas and surgical instruments had varied from 1/18 760 to 1/8 801 in surgical operations at non-speciality acute-care hospitals, corresponding to one case or more each year for a large hospital. It has been presumed that more than 1 500 cases of foreign bodies occur annually in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction usually causes related clinical symptoms and signs shortly after surgery. The second type of response is aseptic with extensive adhesions and encapsulations resulting in a foreign body granuloma [4]. The septic complications are likely to present early during the postoperative period, whereas the aseptic encapsulations can disappear over a period of years, as in the case described here.…”
Section: Discussionmentioning
confidence: 76%